PROBLEMS AND PRACTICAL NEEDS IN LEARNING VOCABULARY IN HIGHER EDUCATION - Ade Nurul Aida; Lalu Thohir; Ahmad Zamzam (Wiralodra English Journal, 2024)
This study analyzed the problems and practical needs of English vocabulary learning among low-score students at a state university in Mataram, Lombok, Indonesia. To provide appropriate instructional materials, learning tasks, or assessment tasks, a need analysis of the student’s prior knowledge is the most important thing that should be done by a teacher. The research involved forty students and used qualitative methods, including questionnaires and interviews, to collect data. The collected data were analyzed using descriptive qualitative methods, such as data reduction, display, analysis, and conclusion. The results of this study show that there are problems in vocabulary learning faced by students such as problems with inaccurate pronunciation, problems in knowing the meaning of too much vocabulary, problems in dealing with grammatical alterations, and problems in using words appropriately. On the other hand, students' practical needs are engaging in learning with interactive activities in the form of games/discussions in class, practicing the words adequately, and asking for feedback for better learning improvement. Future research can further examine overcoming the problems found by linking them directly to practical needs.